Kepastian dan Perlindungan Hukum dalam Pendirian Perseroan Terbatas Melalui Sistem Administrasi Badan Hukum Menurut Undang-Undang Nomor 40 tahun 2007 tentang Perseroan Terbatas - Lany, Arman (Faculty of Law, Padjadjaran University, 2015)
Pengaturan Sistem Administrasi Badan Hukum (SABH) dalam Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas (UUPT) dalam rangka untuk mewujudkan kepastian hukum dan perlindungan hukum bagi para pihak pemangku kepentingan (stakeholders), belum sepenuhnya tercapai. Hal ini disebabkan praktik SABH tidak sejalan dengan pengaturan dalam UUPT dan peraturan pelaksanaan dari SABH telah beberapa kali mengalami perubahan. Fungsi pengesahan akta pendirian PT melalui SABH dalam praktik dihubungkan dengan kepastian hukum dan perlindungan hukum bagi para pihak pemangku kepentingan (stakeholders), hanya untuk memperoleh status badan hukum PT dan belum dilaksanakan sesuai prosedur hukum administrasi negara. Hal ini disebabkan Menkumham sebagai pihak yang berwenang menerbitkan keputusan badan hukum PT tidak melakukan pemeriksaan dokumen dan kelengkapan administrasi pemerintahan dari pemohon. Praktik SABH ke depan dalam pelaksanaan UUPT untuk dapat lebih mewujudkan kepastian hukum dan perlindungan hukum bagi para pihak pemangku kepentingan (stakeholders), harus ada kesesuaian antara pengaturan dan pelaksanaan sehari-hari.Â Legal Certainty and Protection for Stakeholders Concerning the Establishment of Limited Liability Company (PT) through the System of Administrative Of Legal Entity (SABH) Pursuant to Law Number 40 Year 2007 on Limited CompanyÂ AbstractThe regulation for the System Administration of Legal Entity (SABH) in Law number 40 in 2007 on Limited Liability Company to provide legal certainty and protection for stakeholders has not yet been fully realized. This is because the practice of SABH is not accordance with the law on Limited Liability Company. Also, the regulation of the SABH has undergone multiple revisions. The ratification function for establishment of a Limited Liability Company through SABH in order to gain legal certainty and protection is often only done to gain the status of Limited Liability Company, while not heeding the administrative procedure. The Ministry of Law and Human Rights, as a body with the authority to grant the status of Limited Liability Company often does not conduct a proper document and requirement check to fulfill the administrative demand. It is expected in the future that the practice of SABH in the implementation of the Law on Limited Liability Company can also grant legal certainty and protection for the stakeholders; the regulation and the real implementation have to be consistent.Keywords: law certainty, limited company, SABH, limited company law, stakeholders.DOI: https://doi.org/10.22304/pjih.v2n2.a5